Modern outlook on morphological criteria of organ and tissue decellularization - A. S. Sotnichenko; E. A. Gubareva; E. V. Kuevda; I. S. Gumenyuk; I. V. Gilevich; R. Z. Nakokhov; A. A. Slavinskiy; S. N. Alekseenko (Вестник трансплантологии и искусственных органов, 2017)
A rapidly growing development of tissue engineering promotes the increasing interest in the obtainment of various decellularizedtissues and organs. Minimal quality evaluation criteria of obtained tissue engineered constructions have been previously specified. In the discussionpaper the group of authors considers the morphological methods of matrix evaluation applied by various researchers on the model of heart decellularization. The analysis of modern literature and the authors’ own researches have shown that morphological evaluation of decellularization quality has to be complex and should consist of several stages which include both basic and additional evaluation methods.